Mathematical prediction modelling of optimum penalty shot in hockey field / Nur Intan Syafinaz Ahmad ... [et al.] - Ahmad, Nur Intan Syafinaz; Kamarulzaman, Nurul Huda; Ibrahim, Khlipah; Aziz, Ahmad (2013)
Goal in a hockey game can be scored from penalty strokes. In the penalty stroke, only the goalkeeper can stop the ball from entering the goal area. The chance to score a goal depends totally on the ability of the penalty taker to strike the ball efficiently. Due to the pressure experienced by the penalty taker to ensure a goal is scored, it is crucial for him to know the best angle and velocity to shoot the ball. Simple projectile motions theory is used in this paper to determine the best velocity, while the best angle is calculated using right angled triangles and trigonometric ratios.